2020
DOI: 10.1007/s10021-020-00535-2
|View full text |Cite
|
Sign up to set email alerts
|

Local and Regional Drivers of Environmental Changes in Two Subtropical Montane Ponds (Central China) Over the Last Two Centuries

Abstract: The drainage versus seepage hydrologies of each pond were important modulators of primary production.Temperature and nitrogen deposition interacted with local catchment conditions to influence ecosystem response Authors Contributions: XC and SM conceived and designed the study. XC, SM, JP, TZ, XB, and LZ collected and analysed the data. XC and SM wrote the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Even so, this lake zone has probably undergone a transition from a macrophyte‐dominated to algae‐dominated state, with the loss of macrophytes and increase in phytoplankton production driven by cultural eutrophication, elevated lake level, and light limitation (Zhang et al 2016). Third, two lake zones might have responded differently to climate‐related variables (e.g., warming, wind, and extreme weathers) due to their differences in drainage characteristics and ecological regime, as observed in other lake catchments (Maheux et al 2016; Moorhouse et al 2018; Chen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, this lake zone has probably undergone a transition from a macrophyte‐dominated to algae‐dominated state, with the loss of macrophytes and increase in phytoplankton production driven by cultural eutrophication, elevated lake level, and light limitation (Zhang et al 2016). Third, two lake zones might have responded differently to climate‐related variables (e.g., warming, wind, and extreme weathers) due to their differences in drainage characteristics and ecological regime, as observed in other lake catchments (Maheux et al 2016; Moorhouse et al 2018; Chen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Considering lake‐catchment characteristics and ecological regimes as “filters” of multiple stressors can further improve our understanding of catchment‐scale development and context‐dependent ecological responses (Leavitt et al 2009; Maheux et al 2016; Chen et al 2021). Taihu Lake, the third‐largest freshwater and shallow lake in the most densely populated region of eastern China, provides an ideal model system to study how the interaction of anthropogenic activity and climate change over a variety of spatial scales affects lake water quality and ecosystem functioning.…”
mentioning
confidence: 99%
“…This explanation is also supported by recent decreases in C/N ratios in both peat cores, which probably resulted from a larger influx of nitrogen from atmospheric deposition. Furthermore, recent evidence from the nearby Congping Basin (10 km away from Dajiuhu Peatland) revealed that changes in primary producers (diatoms) and consumers (chironomids) of two alpine ponds were closely linked to progressive depletion of δ 15 N, an indicator of enhanced nitrogen deposition (Chen et al, 2021; Zheng et al, 2020). Thirdly, the difference might be linked to human disturbances, which have become one major driving force for peatland degradation (Dise, 2009; Joosten et al, 2012; Poulíčková et al, 2013).…”
Section: Discussionmentioning
confidence: 99%